2017
DOI: 10.1016/j.baga.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology and gender characteristics of hobbyism and punding in Parkinson’s disease: A self-report study

Abstract: Objectives: Dopamine replacement therapy administered to alleviate motor symptoms of Parkinson's disease (PD) has been linked to a range of impulsive and compulsive behaviors (ICBs). The objective of the current study is to describe the phenomenology and delineate gender characteristics of hobbyism and punding in PD based on self-report. Materials and methods: We applied two self-report questionnaires. A clinical and demographic questionnaire assessing motor symptomatology and the short-version of the Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…For instance, prevalence for pathological gambling in PD patients was reported to range between 2.2% and 7% (Santangelo et al ., ). In addition to ICDs, other impulsive/compulsive behaviours have been reported to occur in PD patients, including punding (Spencer, Rickards, Fasano, & Cavanna, ), hobbyism (Callesen & Damholdt, ), walkabouts (Giovannoni, O'Sullivan, Turner, Manson, & Lees, ) and dopamine dysregulation syndrome (DDS), which is a compulsive use of dopamine medications despite adequate motor benefits and the annoying consequences (O'Sullivan, Evans, & Lees, ). These ICD‐related behaviours (e.g., punding and DDS) are considered to have a different pathophysiology than the classical ICDs of gambling, hypersexuality, compulsive eating and compulsive shopping.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, prevalence for pathological gambling in PD patients was reported to range between 2.2% and 7% (Santangelo et al ., ). In addition to ICDs, other impulsive/compulsive behaviours have been reported to occur in PD patients, including punding (Spencer, Rickards, Fasano, & Cavanna, ), hobbyism (Callesen & Damholdt, ), walkabouts (Giovannoni, O'Sullivan, Turner, Manson, & Lees, ) and dopamine dysregulation syndrome (DDS), which is a compulsive use of dopamine medications despite adequate motor benefits and the annoying consequences (O'Sullivan, Evans, & Lees, ). These ICD‐related behaviours (e.g., punding and DDS) are considered to have a different pathophysiology than the classical ICDs of gambling, hypersexuality, compulsive eating and compulsive shopping.…”
Section: Introductionmentioning
confidence: 99%
“…In a case–control study, a higher frequency and increased severity of punding/hobbyism was found in the parkin‐PD group compared to non‐mutated PD group 19 . Male and female patients engaged differently in hobbyism and punding showing different preferences for specific compulsive activities 15 . Males were more likely to be involved in activities such as repairing, dismantling, putting together, and work on projects, whereas females were involved in cleaning, tidying, and sorting objects.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to males, only a few female patients disclosed any ICBs to a clinician, and they only addressed certain symptoms such as compulsive gambling, buying, and eating, but not hobbyism and punding. 15 Psychiatric comorbidities and cognitive impairments were common clinical features in PD patients with punding. One study found that punding was associated with psychiatric comorbidity (ie, psychosis, bipolar disorder) and with addictive behaviors (pathological gambling, DDS).…”
Section: Clinical Features Of Pundingmentioning
confidence: 99%
“…The appearance of punding behavior in animals with preserved nigrostriatal systems and in humans without PD following exposure to drugs of abuse 10 favors this hypothesis. Contradictory findings on the burden of PD symptoms in punding has been published, 21,22 and this finding needs to be replicated by future studies.…”
Section: Discussionmentioning
confidence: 94%